2017
DOI: 10.1080/10410236.2016.1266738
|View full text |Cite
|
Sign up to set email alerts
|

Examining Mechanisms Underlying Fear-Control in the Extended Parallel Process Model

Abstract: This investigation sought to advance the extended parallel process model in important ways by testing associations among the strengths of efficacy and threat appeals with fear as well as two outcomes of fear-control processing, psychological reactance and message minimization. Within the context of print ads admonishing against noise-induced hearing loss (NIHL) and the fictitious Trepidosis virus, partial support was found for the additive model with no support for the multiplicative model. High efficacy appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Given how any persuasive message has the potential to threaten perceived freedoms (Brehm, 1966), and how Quick et al (2018) found evidence that health threats associated with diseases are positively related to freedom threats, and thus likely to generate psychological reactance resulting in defensive message responses (such as counterarguing, source derogation, and boomerang effects), it stands to reason that SARS-CoV-2 messages communicating the risks of the disease and persuading people to take certain action should be expected to pose threats to perceived freedom and to induce psychological reactance along with its typical defensive responses. Thus, beyond health risk perceptions, the present study also examines several variables relevant to the restoration of threatened perceived freedoms; more specifically these include psychological reactance as indexed by perceived threat to freedom, anger, negative cognitions, counterarguing, source derogation, and behavioral intentions to perform recommended behaviors.…”
Section: Threat and Psychological Reactancementioning
confidence: 99%
“…Given how any persuasive message has the potential to threaten perceived freedoms (Brehm, 1966), and how Quick et al (2018) found evidence that health threats associated with diseases are positively related to freedom threats, and thus likely to generate psychological reactance resulting in defensive message responses (such as counterarguing, source derogation, and boomerang effects), it stands to reason that SARS-CoV-2 messages communicating the risks of the disease and persuading people to take certain action should be expected to pose threats to perceived freedom and to induce psychological reactance along with its typical defensive responses. Thus, beyond health risk perceptions, the present study also examines several variables relevant to the restoration of threatened perceived freedoms; more specifically these include psychological reactance as indexed by perceived threat to freedom, anger, negative cognitions, counterarguing, source derogation, and behavioral intentions to perform recommended behaviors.…”
Section: Threat and Psychological Reactancementioning
confidence: 99%
“…Interventions for disease prevention are designed based on theories of engagement in health behaviors. The extended parallel processing model is a main theory in health behavior change (5)(6)(7). The extended parallel processing model is based on the belief that when people are afraid of a threat, they take actions to reduce or control those unpleasant scenarios (7).…”
Section: Introductionmentioning
confidence: 99%
“…The extended parallel processing model is a main theory in health behavior change (5)(6)(7). The extended parallel processing model is based on the belief that when people are afraid of a threat, they take actions to reduce or control those unpleasant scenarios (7). In the extended parallel processing model, perceived susceptibility is an important motivating factor in many healthy behaviors and disease screening.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are further evidence of a gap that exists between theory and practice in road safety campaigns (Cismaru, 2014;Ngondo and Klyueva, 2019). In light of the EPPM and empirical literature, the reliance on threat-based content is critical, as this is likely to impair fear appeal effectiveness (Shen and Coles, 2015;Brennan and Binney, 2010;Quick et al, 2018;Hastings et al, 2004;Aldoory and Bonzo, 2005). Although there is agreement in the literature about the benefits that explicit theory use has for message design in campaign practice, our results illustrate that the barriers to theory application seem to be omnipresent in practice.…”
Section: Neglect Of Efficacy Messagesmentioning
confidence: 56%